2009
DOI: 10.1029/2008ja014019
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐D empirical model of F region Medium‐Scale Traveling Ionospheric Disturbance bands using incoherent scatter radar and all‐sky imaging at Arecibo

Abstract: [1] Perhaps the most persistent and prominent of the midlatitude nighttime F region phenomena observed with all-sky imagers is the Medium-Scale Traveling Ionospheric Disturbances (MSTID) that occur when the geomagnetic activity is low. We introduce a simple empirical 3-D model of these bands, which was developed on the basis of an extension of results given by Seker et al. (2008). Seker et al. (2008) reported observational results on the 3-D geometry of MSTID structures found using combined incoherent scatter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Various techniques exist to measure the horizontal propagation parameters of the waves, with many recent studies making use of broad arrays of dual-frequency GPS receivers to study the propagation of total electron content perturbations [e.g., Afraimovich et al, 1998Afraimovich et al, , 2000Afraimovich et al, , 2003Saito et al, 1998Saito et al, , 2001Hernández-Pajares et al, 2006;Kotake et al, 2006;Nicolls et al, 2004;Tsugawa et al, 2007;Ishida et al, 2008;Ogawa et al, 2009]. All-sky airglow imaging (in particular of the 630 nm OI thermospheric emission) can be used to study the propagation of nighttime MSTIDs [e.g., Mendillo et al, 1997;Garcia et al, 2000;Shiokawa et al, 2003aShiokawa et al, , 2003bShiokawa et al, , 2006Candido et al, 2008;Seker et al, 2009Seker et al, , 2011Martinis et al, 2010]. HF Doppler sounders are also used to study the horizontal parameters and propagation directions of daytime and nighttime TIDs [e.g., Crowley et al, 1987;Crowley and Rodrigues, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques exist to measure the horizontal propagation parameters of the waves, with many recent studies making use of broad arrays of dual-frequency GPS receivers to study the propagation of total electron content perturbations [e.g., Afraimovich et al, 1998Afraimovich et al, , 2000Afraimovich et al, , 2003Saito et al, 1998Saito et al, , 2001Hernández-Pajares et al, 2006;Kotake et al, 2006;Nicolls et al, 2004;Tsugawa et al, 2007;Ishida et al, 2008;Ogawa et al, 2009]. All-sky airglow imaging (in particular of the 630 nm OI thermospheric emission) can be used to study the propagation of nighttime MSTIDs [e.g., Mendillo et al, 1997;Garcia et al, 2000;Shiokawa et al, 2003aShiokawa et al, , 2003bShiokawa et al, , 2006Candido et al, 2008;Seker et al, 2009Seker et al, , 2011Martinis et al, 2010]. HF Doppler sounders are also used to study the horizontal parameters and propagation directions of daytime and nighttime TIDs [e.g., Crowley et al, 1987;Crowley and Rodrigues, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the midnight h m F 2 descended by 50 to 100 km in 85% of the events. The midnight collapse has been investigated by many other researchers, using incoherent scatter radar (ISR) [Behnke and Harper, 1973;Harper, 1979;MacPherson et al, 1998;Seker et al, 2009], airglow techniques [Nelson and Cogger, 1971;Vlasov et al, 2005], and theoretical models [Crary and Forbes, 1986]. Behnke and Harper [1973], MacPherson et al [1998], andVlasov et al [2005] reported the reduction and reversal of the equatorward neutral wind as the basis for the midnight collapse in their observations.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that HmF 2 descends 50 to 100 km in 85 percent of the nights near midnight. This conspicuous phenomenon has been extensively studied using ISR [ Behnke and Harper , 1973; Harper , 1979; MacPherson et al , 1998; Seker et al , 2009], airglow techniques [ Nelson and Cogger , 1971; Vlasov et al , 2005], and theoretical models [ Crary and Forbes , 1986]. Behnke and Harper [1973], MacPherson et al [1998], and Vlasov et al [2005] reported the reduction and reversal of the prevailing equatorward neutral wind being the cause of the midnight collapses they observed.…”
Section: Introductionmentioning
confidence: 99%
“… Behnke and Harper [1973], MacPherson et al [1998], and Vlasov et al [2005] reported the reduction and reversal of the prevailing equatorward neutral wind being the cause of the midnight collapses they observed. The reversal of meridional winds is thought to be due to the pressure bulge associated with the midnight temperature maximum [ Colerico et al , 1996; Seker et al , 2009]. Crary and Forbes [1986], using numerical simulations, and Harper [1979], using two nights of ISR observation, attributed the collapse to the shear in the meridional wind associated with upward propagating semidiurnal tide.…”
Section: Introductionmentioning
confidence: 99%